716 Cell-based virotherapy for targeting cancers. (9th November 2020) - Nguyen, Duong; Gomez, Alberto; Neuharth, Forrest; Alamillo, Ashley; Herrmann, Thomas; Härtl, Barbara; Schneider, Laura; Minev, Ivelina; Minev, Boris; Draganov, Dobrin; Santidrian, Antonio
Abstract : Background: Oncolytic virotherapy has been recognized as a promising new therapy for cancer for decades but only few viruses have been approved worldwide. The therapeutic potential of oncolytic viruses can be severely restricted by innate and adaptive immune barriers making oncolytic virus clinically inefficient. To overcome this obstacle, we utilized adipose-derived stem cells (AD-MSC) loaded with tumor selective CAL1 oncolytic vaccinia virus to generate a new therapeutic agent called SNV1 (SuperNova-1). Methods: CAL1 vaccinia virus was tested for its ability to replicate and selectively kill various human cancer cell lines in vitro and in vivo. Additionally, CAL1 was loaded into adipose-derived mesenchymal stem cells to generate SuperNova1 (SNV1). Both CAL1 and SNV1 were tested for their ability to kill cancer cells in the presence of active complement and neutralizing antibodies in cell culture as well as in mice. Immune cell infiltration of the treated and untreated tumors was analyzed by flow cytometry. Results: CAL1 showed preferential amplification and killed various tested human (PC3, FaDu, MDA-MB-231, RPMI) and mouse cancer cells (CT26, EMT6, TRAMP-C2, RM1). In animals, CAL1 caused tumor regression in PC3 and CT26 mouse models without signs of toxicity. SNV1 significantly enhanced protection of CAL1 virus from clearance by the immune system as compared to naked CAL1 virus, leading to higher therapeutic efficacy in animals. Five days after SNV1 administration, tumor infiltrating lymphocytes (TILs) from both treated and untreated tumors showed increased CD4 and CD8 T-cell infiltrations. Importantly, we documented a decreased frequency of Tregs, and improved effector to Treg ratios, which was associated with inhibition of tumor growth at the treated tumor site and also at distant untreated sites. Conclusions: CAL1 is potentially used as an oncolytic agent. In addition, SNV1 cell-based platform protects and potentiates oncolytic vaccinia virus by circumventing humoral innate and adaptive immune barriers, resulting in enhanced oncolytic virotherapy. Particularly, SNV1 provided instantly active viral particles for immediate infection and simultaneous release of therapeutic proteins in the injected tumors.